Breakthrough Tick-Borne Encephalitis and Epidemiological Trends in an Endemic Region in Poland: A Retrospective Hospital-Based Study, 1988–2020 - Magdalena Sulik-Wakulińska; Kacper Toczyłowski; Sambor Grygorczuk (Vaccines, 2025)
Background/Objectives: Tick-borne encephalitis (TBE) is a notifiable disease in Poland, with the highest incidence in the northeastern region. Although vaccination is highly effective, breakthrough infections occasionally occur. This study aimed to describe the clinical features of vaccinated and unvaccinated TBE cases, assess long-term hospitalization trends, and estimate vaccine effectiveness (VE) in a highly endemic region. Methods: We retrospectively analyzed 1518 laboratory-confirmed TBE cases hospitalized at the University Clinical Hospital in Białystok, Poland, from 1988 to 2020. Clinical and cerebrospinal fluid (CSF) parameters were compared between vaccinated and unvaccinated individuals. Vaccine effectiveness was estimated using the screening method, based on aggregated regional vaccine uptake data from 1999 to 2020. Results: Among all cases, 13 (0.9%) occurred in individuals who had received at least one dose of vaccine, including 4 who had completed the full primary vaccination schedule. Hospitalized vaccinated patients showed similar demographic and clinical characteristics compared to unvaccinated patients, though CSF findings suggested an earlier and more dynamic immune response. Seasonal analysis revealed a sustained increase in TBE hospitalizations and a possible extension of the transmission season into late summer and autumn. Estimated VE was 94.4% (95% CI 85.2–97.9%), though this should be interpreted with caution due to the small number of vaccinated cases and assumptions regarding population-level coverage. Conclusions: This study provides detailed clinical data on breakthrough TBE cases and long-term epidemiological insights from an endemic region in Poland. While vaccine effectiveness appears high, low uptake remains a public health concern. These findings underscore the need for improved vaccination coverage and ongoing surveillance to monitor evolving transmission patterns.